IDENTIFIKASI DAN GAMBARAN INDEKS KEPADATAN LARVA AEDES AEGYPTI DI SEKOLAH TINGGI ILMU KESEHATAN YANG ADA DI BEKASI TAHUN 2021 - Ing Mayfa Situmorang; Nadya Pebrianti Effrata (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Aedes aegypti is the main factor in the transmission of dengue hemorrhagic fever (DHF), according to the WHO distribution during 2010 - 2016 there were an average of 100,000 cases of dengue fever reports. DHF cases in Indonesia in 2016 were recorded at 204,171. The West Java region, precisely in Bekasi City, DHF cases were ranked 2nd with the most DHF cases, while in 2020 in Bekasi Regency from January to February there were 51 cases. This research was conducted at the College of Health Sciences in Bekasi because based on supporting factors such as geographic and demographic factors, the location supports the breeding ground for Aedes larvae. This research method uses a descriptive survey. This research was carried out by placing ovitrap traps and then identifying the trapped larvae using the whole mount method and calculating their density. Based on the research, it was found that there were Aedes aegypti larvae. This shows the risk of spreading dengue disease. Based on the results of the virtual index calculation, the House index (HI) of 0.15% and the Container index (CI) of 1% and Breteau index (BI) of 0.65% of the WHO standard density measure can be stated that the density of aedes aegypti larvae in the College of Health Sciences is in the low category